2016
DOI: 10.1111/pbi.12581
|View full text |Cite
|
Sign up to set email alerts
|

AnAGAMOUSintron‐driven cytotoxin leads to flowerless tobacco and produces no detrimental effects on vegetative growth of either tobacco or poplar

Abstract: SummaryFlowerless trait is highly desirable for poplar because it can prevent pollen‐ and seed‐mediated transgene flow. We have isolated the second intron of PTAG2, an AGAMOUS (AG) orthologue from Populus trichocarpa. By fusing this intron sequence to a minimal 35S promoter sequence, we created two artificial promoters, fPTAG2I (forward orientation of the PTAG2 intron sequence) and rPTAG2I (reverse orientation of the PTAG2 intron sequence). In tobacco, expression of the β‐glucuronidase gene (uidA) demonstrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…To optimize the time needed for robust transient T-DNA expression, tobacco leaf explants inoculated with Agrobacterium (containing the pCAMBIA1305.1 vector) were incubated in the dark at 25 °C for 2, 3, 4, 5, or 6 days. Half of the leaf discs (six) from each treatment were stained for GUS activity 55 . The remaining explants were transferred to solid MS medium containing 150 mg/L timentin to suppress Agrobacterium growth.…”
Section: Methodsmentioning
confidence: 99%
“…To optimize the time needed for robust transient T-DNA expression, tobacco leaf explants inoculated with Agrobacterium (containing the pCAMBIA1305.1 vector) were incubated in the dark at 25 °C for 2, 3, 4, 5, or 6 days. Half of the leaf discs (six) from each treatment were stained for GUS activity 55 . The remaining explants were transferred to solid MS medium containing 150 mg/L timentin to suppress Agrobacterium growth.…”
Section: Methodsmentioning
confidence: 99%
“…A number of molecular confinement strategies have been reported that may block seed and pollen-mediated transgene flow in tree species (Klocko et al, 2018). We have also recently demonstrated that an AGA-MOUS intron-driven expression of a cytotoxin gene can be used to produce flowerless tobacco (Nicotiana benthamiana), and this technique may also be effective in reducing pollen-and seed-mediated transgene flow in poplar (Li et al, 2016). Further, we have reported a transgene deletion technology called the "Gene Deletor" that might be useful in eliminating transgenes from pollen and seeds of poplar, possibly obviating the need for containment (Luo et al, 2007).…”
mentioning
confidence: 98%
“…Transgenic technology has been effectively used to produce poplar trees with a variety of useful traits, including herbicide resistance, biotic and abiotic tolerance, improved growth rate, higher nutrient use efficiency, and improved processing and end-use characteristics (Yang et al, 2009;Chang et al, 2018). Although many transgenic field trials have been carried out in the United States, China, and elsewhere, no transgenic trees have been commercially adopted to our knowledge (Li et al, 2016;Klocko et al, 2018).…”
mentioning
confidence: 99%
“…The qRT-PCR was conducted on the Applied Biosystems 7300, and the volume of reaction was 20 μl, including 10 μl of SYBRR Premix Ex Taq™ (Perfect Real Time; TaKaRa), 0.3 μl (10 pM) of each primer, 1 μl of 10-fold-diluted cDNA and 8.4 μl of sterile double-distilled water. The program for the qRT-PCR were as following: 95 °C for 3 min, 95 °C for 25 s with 35 cycles, 62 °C for 25 s, and 72 °C for 40 s. The UBQ gene was used as control gene to normalize gene expression 52 . The relative expression level of genes was analyzed with the 2 −ΔΔCt method, which represented the difference of the cycle threshold (Ct) between the control UBQ products and target gene products.…”
Section: Methodsmentioning
confidence: 99%